2001
DOI: 10.1046/j.1365-2257.2001.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin-induced skin necrosis associated with Factor V Leiden and protein S deficiency

Abstract: Thrombotic events are rare complications during anticoagulation therapy. The thrombosis varies from localized cutaneous involvement to catastrophic thromboembolism and is usually associated with an underlying thrombophilia. We describe a patient who developed skin necrosis during warfarin treatment for a pulmonary thromboembolism. The management was complicated by the development of heparin-induced thrombocytopenia and further thrombotic events. Thrombophilia screen demonstrated the presence of protein S defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Further testing for a thrombophilic state revealed the combined presence of heparin-dependent platelet-activating (HIT) antibodies and functional protein S deficiency [13]. Factor V Leiden mutation has also been described as a contributory cause for warfarin-induced skin necrosis in a patient who also had heparin antibodies and protein S deficiency [14]. In the context of the current case, it bears mentioning that cancer by itself causes hypercoagulability [15].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Further testing for a thrombophilic state revealed the combined presence of heparin-dependent platelet-activating (HIT) antibodies and functional protein S deficiency [13]. Factor V Leiden mutation has also been described as a contributory cause for warfarin-induced skin necrosis in a patient who also had heparin antibodies and protein S deficiency [14]. In the context of the current case, it bears mentioning that cancer by itself causes hypercoagulability [15].…”
Section: Discussionmentioning
confidence: 75%
“…It should be noted that HIT antibodies may also contribute to this process as most patients who receive warfarin have also received heparin. This is exemplified by recent case reports of skin necrosis in patients treated with warfarin who also have had HIT [14,17].Thus, ''anticoagulant-induced skin necrosis'' may be a better term for this entity.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, it begins on day 3–6 after initiating warfarin 7. It is also thought that the precipitous reduction in the concentration of protein C and protein S creates a hypercoagulable state, which cause thrombotic occlusions of the microvasculature with resulting necrosis of the subcutaneous fat 7,8…”
Section: Discussionmentioning
confidence: 99%
“…Similar are the histological findings noted in warfarin-induced skin necrosis. In these cases, necrotic skin lesions soon after treatment with warfarin are due to paradoxical hypercoagulability noted several days after initiation of treatment with warfarin [12]. Although studies have shown that a very high proportion of patients with of TTP have a deficiency of von Willebrand factorcleaving protease, the pathogenic mechanisms underlying the rest of TMA syndromes seem to involve a wide range of quantitative and qualitative abnormalities of hemostatic factors [13].…”
Section: Discussionmentioning
confidence: 99%